2015
DOI: 10.1504/ejie.2015.069343
|View full text |Cite
|
Sign up to set email alerts
|

Balancing parallel assembly lines with disabled workers

Abstract: In this paper we study an assembly line balancing problem that occurs in sheltered worker centers for the disabled, where workers with very different characteristics are present. We are interested in the situation in which complete parallel assembly lines are allowed and name the resulting problem as parallel assembly line worker assignment and balancing problem (PALWABP). This approach enables many new possible worker-tasks assignments, what is beneficial in terms of both labour integration and productivity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…It should be noted that studies that considered workers' differences in terms of disability were also found. Since the pioneering study by Miralles et al (2007), the integration of workers with disabilities in assembly line balancing and worker assignment has received considerable attention among researchers (Araújo, Costa, and Miralles 2012;Borba and Ritt 2014;Castellucci and Costa 2015;Cortez and Costa 2015), including variants of such topic, such as disabled-friendly job rotation objectives (Costa and Miralles 2009), line layouts (Araújo, Costa, and Miralles 2015) and more general industrial settings, extrapolating data from sheltered work centres for the disabled (Moreira, Miralles, and Costa 2015). However, we did not include this topic in our research keywords as our objective was to study the general framework of workers' differences.…”
Section: Database and Abstract Selectionmentioning
confidence: 99%
“…It should be noted that studies that considered workers' differences in terms of disability were also found. Since the pioneering study by Miralles et al (2007), the integration of workers with disabilities in assembly line balancing and worker assignment has received considerable attention among researchers (Araújo, Costa, and Miralles 2012;Borba and Ritt 2014;Castellucci and Costa 2015;Cortez and Costa 2015), including variants of such topic, such as disabled-friendly job rotation objectives (Costa and Miralles 2009), line layouts (Araújo, Costa, and Miralles 2015) and more general industrial settings, extrapolating data from sheltered work centres for the disabled (Moreira, Miralles, and Costa 2015). However, we did not include this topic in our research keywords as our objective was to study the general framework of workers' differences.…”
Section: Database and Abstract Selectionmentioning
confidence: 99%
“…In manual assembly lines it is common to have operators with different skills levels performing a task, which means that the line efficiency may vary according to worker assignment. Authors such as Araújo et al (2015), Esmaeilian et al (2015), Chutima and Yothaboriban (2017) and Çil et al (2017), considered this factor in their studies dealing with the PS. In contrast, in PT and PU, no study considering the operators' skill levels has been proposed.…”
Section: Operators With Different Skill Levelsmentioning
confidence: 99%
“…Miralles et al (2007) have proposed the ALWABP motivated by the situation found in sheltered work centers for the disabled, in which assembly lines are operated by workers with disabilities. This problem has fomented an intense amount of research both on the original problem (Blum & Miralles 2011, Moreira et al 2012, Mutlu et al 2013, Vilà & Pereira 2014, Borba & Ritt 2014 and on its variants (Costa & Miralles 2009, Araújo et al 2012, Moreira & Costa 2013, Araújo et al 2014.…”
Section: Min Cmentioning
confidence: 99%